Trichome structure and evolution in Neotropical lianas - Nogueira, Anselmo; Leite El Ottra, Juliana Hanna; Guimares, Elza [UNESP]; Machado, Silvia Rodrigues [UNESP]; Lohmann, Lucia G. (Oxford University Press, 2013)
Trichomes are epidermal outgrowths generally associated with protection against herbivores and/or desiccation that are widely distributed from ferns to angiosperms. Patterns of topological variation and morphological evolution of trichomes are still scarce in the literature, preventing valid comparisons across taxa. This study integrates detailed morphoanatomical data and the evolutionary history of the tribe Bignonieae (Bignoniaceae) in order to gain a better understanding of current diversity and evolution of trichome types.Two sampling schemes were used to characterize trichome types: (1) macromorphological characterization of all 105 species currently included in Bignonieae; and (2) micromorphological characterization of 16 selected species. Individual trichome morphotypes were coded as binary in each vegetative plant part, and trichome density and size were coded as multistate. Ancestral character state reconstructions were conducted using maximum likelihood (ML) assumptions.Two main functional trichome categories were found: non-glandular and glandular. In glandular trichomes, three morphotypes were recognized: peltate (Pg), stipitate (Sg) and patelliform/cupular (P/Cg) trichomes. Non-glandular trichomes were uniseriate, uni- or multicellular and simple or branched. Pg and P/Cg trichomes were multicellular and non-vascularized with three clearly distinct cell layers. Sg trichomes were multicellular, uniseriate and long-stalked. ML ancestral character state reconstructions suggested that the most recent common ancestor (MRCA) of Bignonieae probably had non-glandular, Pg and P/Cg trichomes, with each trichome type presenting alternative histories of appearance on the different plant parts. For example, the MRCA of Bignonieae probably had non-glandular trichomes on the stems, prophylls, petiole, petiolule and leaflet veins while P/Cg trichomes were restricted to leaflet blades. Sg trichomes were not present in the MRCA of Bignonieae independently of the position of these trichomes. These trichomes had at least eight independent origins in tribe.The patterns of trichome evolution indicate that most morphotypes are probably homologous in Bignonieae and could be treated under the same name based on its morphological similarity and common evolutionary history, in spite of the plethora of names that have been previously designated in the literature. The trichome descriptions presented here will facilitate comparisons across taxa, allowing inferences on the relationsthips between trichome variants and future studies about their functional properties.
Keywords: Bignoniaceae; Brazil; EFNs; Extrafloral nectaries; Glands; Insectplant interactions; Morphological evolution; Trichomes; Vines